Nowa przedsiębiorczość warunkiem skuteczności firmy - Kołodziejski, Janusz (Modern Entrepreneurship as a Condition of the Company Effectiveness, 2006)
A sample group of one hundred people from small and medium enterprises, which operate in the area of Częstochowa and in its region was investigated. The ground was prepared with the help of questionnaire containing yes/no queries. Now, the collected material is being statistically formulated, and the full compilation will be presented after the whole process is finished. In short, the research was to show some aspects of an area, and a position occupied by employees in their workplace.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 329-336